Addendum zu 1‐Butanol [BAT Value Documentation in German language, 2016]. Issue 3 (25th July 2016) - Weistenhöfer, W.; Leng, G.; Drexler, H.; Hartwig, A.; ,
1‐Butanol (n‐Butyl alcohol): Addendum BAT value documentation (2016): The German Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area has re‐evaluated the biological tolerance value at the work place (BAT value) for 1‐butanol. A capillary gas chromatographic head space technique developed by the Working Group "Analyses in Biological Materials" of the German Research Foundation (DFG) was used for determining 1‐butanol in urine. For this method hydrolysis is recommended neither for blood nor for urine investigation. The BAT values of 10 mg 1‐butanol/g creatinine (sampling time at the end of exposure or end of shift) and 2 mg 1‐butanol/g creatinine (sampling time 16 hours after the end of shift (at the beginning of the next shift)) related to the MAK value of 100 ml/m 3 were confirmed.